L’exercice politique de la bourgeoisie : les assemblées de la Ville de Paris de 1528 à 1679 - Michel Demonet; Robert Descimon (Les Cahiers de Framespa)
Using a particular institution, the City assemblies, this article intends to raise the issue that the system of political representation which was specific to Parisian bourgeoisie went through significant changes between 1528 and 1679. The very large number of individuals observed during this period permits refined and more detailed statistical analysis. This investigation enables both social description of Parisian bourgeoisie (for many years divided between merchants and royal officers) and analysis of political functioning (a small number of notables specialized in municipal administration took up the appointments).